2019
DOI: 10.1002/pbc.28012
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to minimize radiation burden in infants and high‐risk medulloblastoma using intrathecal methotrexate and high‐dose chemotherapy: A prospective registry study in Japan

Abstract: Background Most childhood medulloblastoma (MB) cases are curable using multimodal treatment, including craniospinal irradiation (CSI). However, late effects are a serious problem for survivors. This prospective registry study evaluated Japanese patients to determine whether a reduced radiation dose was feasible. Patients and Methods Patients with MB were classified as an infant group (<3 years old) and a high‐risk (HR) group (≥3 years old with metastasis). The HR group received intrathecal methotrexate (IT‐MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
(105 reference statements)
0
19
0
Order By: Relevance
“…However, it still gave promising results since there were no disease recurrences during a long‐term follow up. We have previously reported that HDC consisting of thiotepa and melphalan demonstrated antitumor activity against several types of tumors including MB, 7,9 and the registry data previously reported by us showed excellent results (5‐year PFS 82.1 ± 7.2% and 5‐year OS 85.7 ± 6.6%) in 28 high‐risk MB patients. Taken together, this strongly suggests that HDC not only allows the radiation dose to be reduced to 18 Gy but also significantly improves survival.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, it still gave promising results since there were no disease recurrences during a long‐term follow up. We have previously reported that HDC consisting of thiotepa and melphalan demonstrated antitumor activity against several types of tumors including MB, 7,9 and the registry data previously reported by us showed excellent results (5‐year PFS 82.1 ± 7.2% and 5‐year OS 85.7 ± 6.6%) in 28 high‐risk MB patients. Taken together, this strongly suggests that HDC not only allows the radiation dose to be reduced to 18 Gy but also significantly improves survival.…”
Section: Discussionmentioning
confidence: 55%
“…The results of this study of reduced‐dose CSI 18 Gy for children with newly diagnosed MB, which was based on a previous phase II trial prospective registry study, 7 showed a promising 5‐year PFS rate of 83.9 ± 6.7% for average‐risk patients. Simultaneous radiotherapy with the second and third courses of chemotherapy may raise the antitumor effect of treatment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…(2019) reported toxicity profiles of this regimen in a further cohort 9 . Recently, a promising result of this regimen for high‐risk medulloblastoma was published 10 . By contrast, few studies have investigated this regimen for high‐risk neuroblastoma 11 .…”
Section: Introductionmentioning
confidence: 99%